Tandem gene amplification restores photosystem II accumulation in cytochrome b559 mutants of cyanobacteria - Chiu, Yi-Fang; Fu, Han-Yi; Skotnicová, Petra; Lin, Keng-Min; Komenda, Josef; Chu, Hsiu-An (The New phytologist, 2022)
Cytochrome (Cyt) b559 is a key component of the photosystem II complex (PSII) that is essential for its proper functioning and assembly. Site-directed mutants of the model cyanobacterium Synechocystis sp. PCC6803 with mutated heme axial ligands of Cyt b559 have little PSII and are therefore unable to grow photoautotrophically. Here we describe two types of Synechocystis autotrophic transformants that retained the same mutations in Cyt b559 but are able to accumulate PSII and grow photoautotrophically. Whole-genome sequencing revealed that all of these autotrophic transformants carried a variable number of tandem repeats (from 5 to 15) of chromosomal segments containing the psbEFLJ operon. RNA-seq analysis showed greatly increased transcript levels of the psbEFLJ operon in these autotrophic transformants. Multiple copies of the psbEFLJ operon in these transformants were only maintained during autotrophic growth, while its copy numbers gradually decreased under photoheterotrophic conditions. Two-dimensional PAGE analysis of membrane proteins revealed a strong deficiency in PSII complexes in the Cyt b559 mutants that was reversed in the autotrophic transformants. These results illustrate how tandem gene amplification restores PSII accumulation and photoautotrophic growth in Cyt b559 mutants of cyanobacteria, and may serve as an important adaptive mechanism for cyanobacterial survival.
Keywords: cytochrome b559; amplifikace genu; Photosystem II Protein Complex; cyanobacterium; Synechocystis; photosynthesis; cytochromy b; Cytochrome b Group; cytochromy typu b; photosystem II (PSII); Cytochromes b; tandem gene amplification; Gene Amplification; fotosystém II (proteinový komplex)